(3GdNWHI GdRgQGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SHMGf Gdedc GdbgGQ GdBdI GdLHGQ dGJOQcg GdCHUGQ s
(3BNQgG (B:s
(3hGdJfHjg Yf GdZadI hGaGVI GdgOGjI hcTa GdTHgI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH (B((3COH JjehQ (B482) s
Keywords: (3GdadSaI hGdefWbs